Treatment of acute lymphoblastic leukemia with protocol Hongkong-Indonesia Acute Lymphoblastic Leukemia 97 - Johannes Bondan Lukito (Indonesian Pediatric Society Publishing House, 2007)
Background The HK-Ina ALL 97 study protocol is based on the Therapy Study ALL-BFM 95 protocol. Basically, this protocol stratifies the patients into three groups, i.e. standard risk for low risk group (SR), intermediate risk (IR), and high risk (HR) group, and the treatment is directed according to the risk groups. Objectives To investigate the overall treatment result of childhood ALL in Indonesia and to stratify patients according to biological, clinical criteria, and molecular study that identify the standard and high risk patients with greater precision. Methods Twenty patients entered in this study; 10 SR, 6 IR and 4 HR groups. Induction phase for SR group consisted of four drugs (phase I'a) for five weeks and three drugs combination (phase I'b) for four weeks. Consolidation phase consisted of four doses of mini- HD MTX (2 gram/m 2 ) (protocol M'), reinduction phase used dexamethasone for seven weeks, and maintenance phase consisted of 6 MP and MTX. Boys, who were at higher risk of relapse, were given pulse dexamethasone and vincristine. Induction phase for IR was the same as SR, but four doses of daunorubicin were given to IR group (Ia). Consolidation phase included four doses HDMTX (5 gram/m 2 ). Phase Ib and Protocol II was the same as SR group. Pulse dexamethasone and vincristine was given to all patients. Induction phase for HR group will be the same as IR group. This followed by three blocks of very intensive treatment. Two reinduction phases and maintenance was the same as SR and IR groups. Results Nineteen of 20 patients achieved complete remission (CR). The patient who could not stand was a 10 years old boy with initial WBC 612X10 9 /L, T-lineage marrow. He died 5 months since the initial diagnosis after treated with HDMTX with dominant CD33 and sepsis. Conclusion The EFS in this study is 95% for the observation of 5 months through five years and two months. It is still expected that the result fall off in the subsequent year, but it is also expected to be comparable to 70-80%. The very intensive and toxic program for HR group, may improve the EFS, but may also cause secondary AML in the earlier time.